Development and testing of a rent determination framework for PPP rental villages. Issue 2 (8th March 2022) - Liu, Shijing; Jin, Hongyu; Liu, Chunlu; Xie, Benzheng; Mills, Anthony
Abstract: With the growing ageing population, a range of supported housing styles for seniors with more complex needs is required in order to cater for a broad stream of circumstances. Decreased government involvement and affordability issues set thresholds for seniors to enter the appropriate retirement housing such as rental villages. Public–private partnership (PPP) is widely used to construct public infrastructure by integrating public welfare and commercial projects. PPPs have, however, not yet been studied or put into effect for rental villages. Concession rent is one of the key factors that affect the success of PPP rental villages. This article proposes PPP as an initiative for rental villages that meet seniors' need for appropriate retirement housing, then develops a framework for rent determination of PPP rental villages and examines this framework based on an invented example. The framework is established for PPP rental villages based on cost–benefit analysis in order to set the rent in consideration of the key factors such as government subsidy, operation cost, concession period and expected rate of return. Two scenarios under the PPP process with different government subsidies are presented for comparison with the conventional approach. An empirical example, developed from an existing rental village in Geelong, is used to numerically verify the framework. A sensitivity analysis is conducted to explore the impacts of three variables on the rent: the operation cost, the number of occupied units and the percentage of rental income, and then to discuss scenarios whereby the government's early investment during the construction period can result in a lower rent. The results show that, compared to the conventional approach, the construction of rental villages by applying PPP can effectively reduce the rent to improve affordability for seniors. The development of PPP rental villages could have long-term prospects when well integrated with a government subsidy. The research findings will significantly facilitate the rent determination process of PPP rental villages and satisfy the interests of the government, private sectors and the seniors. The article highlights the importance of PPP rental villages and also provides a guide to other similar PPP projects such as social housing and aged care facilities.